2020
DOI: 10.1038/s41598-020-76773-0
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual variability of eGFR trajectories in early diabetic kidney disease and lack of performance of prognostic biomarkers

Abstract: Studies reporting on biomarkers aiming to predict adverse renal outcomes in patients with type 2 diabetes and kidney disease (DKD) conventionally define a surrogate endpoint either as a percentage of decrease of eGFR (e.g. ≥ 30%) or an absolute decline (e.g. ≥ 5 ml/min/year). The application of those study results in clinical practise however relies on the assumption of a linear and intra-individually stable progression of DKD. We studied 860 patients of the PROVALID study and 178 of an independent population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…However, patterns of eGFR decline, which are called trajectories of eGFR, vary between patients. 30 A report from six large-scale, randomised controlled trials revealed that more cases presented with non-linear eGFR decline among diabetes patients. 31 Many reports have demonstrated risk factors related to the decline in eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…However, patterns of eGFR decline, which are called trajectories of eGFR, vary between patients. 30 A report from six large-scale, randomised controlled trials revealed that more cases presented with non-linear eGFR decline among diabetes patients. 31 Many reports have demonstrated risk factors related to the decline in eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach suffers from several shortcomings. First, individual eGFR slopes can only be estimated very inaccurately, as only very few data points at non-equidistant time points are available for each patient [5]. Moreover, the categorization of the resulting eGFR slopes adds another layer of possible bias as it leads to subjects close on the continuous spectrum but on the opposite sides of the cutpoint being characterized as different [31].…”
Section: Discussionmentioning
confidence: 99%
“…4 Department of Nephrology, University of Regensburg, University Hospital Regensburg, Regensburg, Germany. 5 Department of Nephrology and Medical Intensive Care, Charité Universitätsmedizin Berlin, Berlin, Germany. 6 Department of Internal Medicine IV (Nephrology and Hypertension), Medical University Innsbruck, Innsbruck, Austria.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] In our study though eGFR was not significantly different in the two groups; with and without DN, serum creatinine levels were a risk in both sexes and eGFR negatively correlated with UACR in males as shown in Table-4. As eGFR is closely related to age, baseline eGFR at the time of diagnosis of T2DM and further monitoring to see the rate of decline [16] is imperative for initiating treatment with antidiabetic agents which will protect the kidneys also. [12] In our study, the serum lipids were not statistically different in the two groups, yet studies have shown that HDL and TG are independent risk factors for cardiovascular disease, systolic blood pressure (SBP) being the measure.…”
Section: Discussionmentioning
confidence: 99%